TOPICAL ISSUES OF FUNCTIONING A REGION AS A SOCIAL-ECONOMIC SYSTEM - R. A. Timofeyev; V. V. Shlychkov; I. G. Alafuzov (Russian Journal of Economics and Law, 2015)
Objective: to identify the topical issues of forming a region as a social-economic system. Methods: systematic approach, based on general scientific methods of empirical and theoretical research such as observation and comparison, analysis and synthesis, induction and deduction, as well as comparative-historical method, statistical methods, macroeconomic analysis. Results: the major issues of applying a systematic approach to the analysis of the region as a socio-economic system were explored and analyzed. The authors proved the most important features of the system; considered different points of view on the content of the region as a system category; analyzed the basic paradigm of the region functioning; identified specific properties inherent to the region as a system; conducted analysis of the modern Russian and foreign literature, which showed that at present there is no consensus about the structural content of the region as an economic system at meso-level; suggested the authors’ definition of the region category; conclusions were made about the applicability of systematic approach to analyzing a region as a socio-economic system. Scientific novelty:the trends and problems of the region formation as an economic system were specifiedin the form of components of a single social and economic system; the conceptual scheme for the region development as a socio-economic system at meso-level was proposed; the author's definition of the regionwas given. The suggested conceptual framework focuses on regional subsystems, each of which is characterized by resources (capacity), the effective use of which is intended to ensure the sustainable and competitive territory development, while increasing the quality of life of the population under federalism and globalization. Practical significance: conclusions and suggestions can be used by public authorities in the strategic policy development for the effective management of the Russian regions.